KARAKTERISTIK PENDERITA KANKER PAYUDARA RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2014-2016 - Susi Nurianti Sitinjak; Fazidah A Lubis; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Breast cancer is the second ranked cancer in the world. Based on The National Cancer Institute (2017), the proportion of breast cancer by 15% of all new cases of cancer and breast cancer mortality proportion amounted to 6,8% of all cancer deaths. Data were 160 patients of breast cancer who hospitalized at Santa Elisabeth Hospital Medan in 2014-2016. The purpose of this study was to determine the characteristics patients of breast cancer who hospitalized at Santa Elisabeth Hospital Medan in 2014-2016. This is descriptive study with case series design. Population is all data of patients breast cancer which are 160 and sample as well as the total population. Data was analyzed by Chi- square, Mann-Whitney, Kolmogorov-Smirnov and Kruskal-Wallis. The result show the highest propotion of breast cancer patient at the age of 41-65 years (76,3%), woman (100%), Bataknese (78,1%), Protestant (60,6%), housewife (38,8%), married (93,1%), residence outside Medan (60,6%), the main complaiment lump of breast (49,4%), stage IV (25%), operation (68,1%), length of treatment on avarage 6 days, home ambulatory (92,5%). There is no significant difference based age and clinical stage (p>0,05). There is a significant difference based average length of treatment and clinical stage (p<0,05). It was recommended that Santa Elisabeth Hospital should complicated the data of patients. Patients and community should do breast self-examination (SADARI) to detected the breast cancer. Key words : Breast Cancer, Patient Characteristics, Santa Elisabeth Hospital